Unheard music from the interwar period - Kahn, Erich Itor 1905-1956; Susskind, Walter 1913-1980; Hauer, Josef Matthias 1883-1959; Garden, Anthony 1891-1963; Gruenberg, Louis 1884-1964 (Channel Classics, 2017)
The Ebony Quartet plays music by Khan, Süsskind, Hauer, Jokl, and Gruenberg
Interpreten: Barbara Kozelj, soprano. Daniel Reuss, narrator. Ebony Quartet (Marleen Asberg, Anna De Vey Mestdagh, violins; Roland Krämer, viola; Daniel Esser, cello
Aufnahmen: 2016 und 2017, Keizersgrachtkerk, Amsterdam
Keywords: String quartets; Monologues with music (String quartet); Songs (High voice) with string quartet; Monologues (Music); Songs; CD